Hungarian Monitoring, 29 July 1989 . [Magyar rádiófigyelő], 1989. július 29 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Polish United Workers' Party Central Committee in session - Nationalities in the USSR: problems - Gorbachev criticized at first meeting of Soviet representatives Domestic Affairs: - The Petőfi case - Interim elections in Szeged - 10th congress of the European Baptist Federation - Welt am Sonntag: siege situation exists at FRG Budapest embassy stormed by GDR refugees - Billy Graham holds sermon in Népstadion Economy: - Will there be a Hungarian car? Will there be Rába-Opel cooperation? Külpolitika: - LEMP KB ülés - A SZU-beli nemzetiség: problémák - Gorbacsovot bírálják a szovjet képviselők első tanácskozásán Belpolitika: - A Petőfi - Ügy - Szegedi időszaki választás - Az Európai Baptista Szövetség 10. kongresszusa - A Welt am Sonntag című lap szerint, valóságos ostromállapot uralkodik az NSZK budapesti nagykövetségén, amelyet megrohamoztak az NDK-beli menekültek - Billy Graham Népstadionban tartott igehirdetése Gazdaság: - Lesz-e magyar autó? Lesz-e Rába-Opel kooperáció?